Universal software system requirements classification - Shekhovtsov, V.; Kostanyan, A. (Українські технології, 2006)
This paper presents new requirements classification. It’s more flexible than traditional functional and nonfunctional requirements division. Classification model is based on modern faceted approach and used International Standardization Organization software quality model. Join universal model with improvements and usage examples is introduced.
Keywords: system requirements; faceted approach; ISO software quality model